Website communications for campus sustainability: an analysis of Canadian universities. Issue 3 (12th February 2020) - Amey, Leaya; Plummer, Ryan; Pickering, Gary
Abstract : Purpose: This study aims to better understand the communication of sustainability by Canadian universities, specifically the use of websites, interactive features and sustainability plans. Design/methodology/approach: A total of 95 Canadian universities were included in this study. The mixed-methods approach sought to capture the communication of sustainability via websites, the interactive features used, as well as to evaluate the quality of sustainability plans. Findings: The study revealed that 67% of universities address sustainability on their websites. On average, universities offer three to four interactive features on their sustainability-related Web pages, and the average score of the quality of campus sustainability plans was 29 (out of 41). Research limitations/implications: This study does not investigate the extent to which interactive features enhance the involvement and participation in sustainability efforts or the extent to which the sustainability plans were put into practice by universities. Practical implications: The findings assist with understanding how higher education institutions (HEIs) can enhance their sustainability communication via their websites to encourage interaction and engagement in campus sustainability. The findings can also help universities to enhance the effectiveness of sustainability plans. Originality/value: To the best of the authors' knowledge, this is the first research to assess sustainability content and the interactive features on sustainability-related pages of Canadian universities' websites. The quality of sustainability plans is also evaluated. The study informs the present understanding of communicating sustainability by Canadian universities and provides a basis for future investigations in HEIs in Canada and beyond.